Control of imploded core plasma by changing beam arrangement of Gekko XII. (March 2016) - Koga, M; Ishii, Y; Sogo, T; Shiraga, H; Nagatomo, H; Ozaki, T; Fujioka, S; Azechi, H
Abstract: We proposed the new laser arrangement to implode a target, a 12-beam implosion, and tried it in a fast ignition integration experiments. The concept of the 12-beam implosion is as follows. The three laser beams near a cone are shifted not to irradiate a cone and a long gold cone is used to prevent the irradiation of those three laser beams with fundamental frequency. In experiments, time-resolved two-dimensional X-ray images of an imploded core plasma were obtained by an X-ray framing camera. It is found that the spherical symmetry of the imploded core plasma is improved and the motion of the imploded core plasma towards the cone is suppressed in half in the 12-beam implosion. We believe that the 12-beam implosion will become a useful concept in controlling the imploded core plasma.